Prolonged grief in refugees, parenting behaviour and children's mental health. (September 2021) - Bryant, Richard A; Edwards, Ben; Creamer, Mark; O'Donnell, Meaghan; Forbes, David; Felmingham, Kim L; Silove, Derrick; Steel, Zachary; McFarlane, Alexander C; Van Hooff, Miranda; Nickerson, Angela; Hadzi-Pavlovic, Dusan
Background: Many refugees experience bereavement, and as a result they suffer elevated rates of prolonged grief disorder. Evidence also indicates that elevated rates of psychological disturbance in refugee children can be associated with parental mental health. This study examined the extent to which prolonged grief disorder in refugees is associated with their parenting behaviour and in turn with their children's mental health. Methods: This study recruited participants from the Building a New Life in Australia prospective cohort study of refugees admitted to Australia between October 2013 and February 2014. The current data were collected in 2015–2016 and comprised 1799 adults, as well as 411 children of the adult respondents. Adult refugees were assessed for trauma history, post-migration difficulties, harsh and warm parenting, probable prolonged grief disorder and posttraumatic stress disorder. Children were administered the Strengths and Difficulties Questionnaire. The current analyses on bereaved refugees comprise 110 caregivers and 178 children. Results: In this cohort, 37% of bereaved refugees reported probable prolonged grief disorder. Path analysis indicated that caregivers' grief was directly associated with children's emotional difficulties. Caregiver warmth was associated with reduced emotional problems in children of refugees with minimal grief but associated with more emotional problems in caregivers with more severe grief. More harsh parenting was associated with children's conduct problems, and this was more evident in those with less severe grief. Conclusion: Severity of prolonged grief disorder is directly linked to refugee children's mental health. The association between parenting style, grief severity and children's mental health highlights that managing grief reactions in refugees can benefit both refugees and their children.